Simulating the economic impact emerging from the strategic decision-making of firms: A macroeconomic agent-based model - Giovannoni, Amalio Dino John (Rhodes University, Faculty of Commerce, Rhodes Business School)
The key research problem addressed in this project is: how does the strategic decision making of firms affect an economy? While this is a difficult question to answer, insights may be gained through the use of computational techniques such as agent-based modelling (ABM). An agent-based model is developed that simulates micro-level economic interactions between individuals and _rms in different markets, resulting in emergent macro-level features. Technological progress is an important determinant of economic growth and has been decomposed into two complementary factors: knowledge and technological sophistication. The model is used to explore the long-term, macroeconomic consequences of _rms investing more heavily in knowledge development. The simulations show that a shift towards a knowledge-based economy (KBE) has an insignificant impact on GDP over the long-term. However, the shift does produce a significant increase in unemployment. The higher unemployment is shown to be particularly high for the unskilled sectors of the population. It is therefore paramount that companies embark on skills development, training and educational initiatives when following a path of technological and knowledge innovation. A transformation of the education system to one that is inclusive, focused on quality, adaptive, encourages creativity, aligned with the needs of industry, and stimulates R&D is crucial. Without a coordinated strategy between industry, academia, and government in attempts to achieve a KBE, economic growth may be constrained, while the levels of unemployment, inequality and poverty may deteriorate.
Keywords: Decision making -- Economic aspects; Industrial management -- Decision making; Industrial management -- Computer simulation; Knowledge economy; Technological unemployment; Economic development -- Computer simulation; Employees -- Training of